Intra-rater reliability, inter-rater reliability and minimal detectable change of the Posterior Shoulder Endurance Test in elite athletes - Powell, A.; Levy, E.; Heneghan, N. R.; Horsley, I. (Physical Therapy in Sport, 2021)
Objective: Investigate intra-rater and inter-rater reliability of the posterior shoulder endurance test (PSET) and calculate minimal detectable change (MDC) to establish measurement properties and inform use of the PSET in practice.